Relative toxicity of gossypol enantiomers in broilers - Lordelo, M.M. (2009)
Use of cottonseed meal in poultry diets has been avoided in large part because of fear of gossypol toxicity. Gossypol exists naturally as a mixture of 2 enantiomers that exhibit different biological activities. Two experiments were conducted to determine the relative toxicity of gossypol enantiomers on broilers. In the first experiment, 3-d-old broilers were fed a standard diet containing 0, 100, 200, 300, or 400 mg of gossypol from gossypol acetic acid per kilogram of diet from 3 to 42 d of age. This form of gossypol contains both enantiomers in an equimolar ratio. Each dietary treatment consisted of 6 replicate pens of 4 birds. In the second experiment, 3-dold broilers were divided into 15 pens of 4 birds each and fed a standard diet supplemented with either no gossypol or one of the gossypol enantiomers at 200 or 400 mg/kg of diet from 3 to 21 d of age. In both experiments, feed intake and BW gain were measured. In addi- (Key words: cottonseed meal, gossypol, gossypol enantiomer, broiler) 2005 Poultry Science 84:1376–1382 INTRODUCTION Cottonseed meal (CSM) could be an attractive alternative protein source for poultry diets, but concern over the presence of the potentially toxic agent, gossypol, has limited its use. Gossypol [1,1′,6,6′,7,7′-hexahydroxy-5,5′- diisopropyl-3, 3′-dimethyl-(2, 2′- binaphthalene)-8, 8′-dicarboxaldehyde] is a polyphenolic compound located in pigment glands that are distributed throughout the cotton plant. Gossypol is composed of 2 naphthalene rings with restricted rotation around the bond connecting the rings. As a result of this restricted rotation, gossypol occurs naturally as a mixture of 2 enantiomers [(+)- and (−)- 2005 Poultry Science Association, Inc. Received for publication February 7, 2005. Accepted for publication May 5, 2005. 1This research was supported in part by grant 2631RE683-118 from the Georgia Cotton Commission, Perry, GA. 2Mention of trade names or commercial products in this article is solely for the purpose of providing specific information and does not imply recommendation or endorsement by the US Department of Agriculture. 3To whom correspondence should be addressed: ajdavis@uga.edu. 1376 tion, several organ and tissue samples were collected at 21 d (experiments 1 and 2) and 42 d (experiment 1) of age and analyzed for gossypol. In experiment 1, feed consumption and BW gain were reduced (P < 0.05) at 21 and 42 d for the birds fed the highest level of gossypol. The concentration of gossypol in the heart, kidney, and plasma were equivalent at 21 and 42 d of age. In experiment 2, total feed consumption was reduced only in birds consuming (−)-gossypol, but BW gains were lower for birds fed either enantiomer. However, (−)-gossypol was more detrimental to growth than (+)-gossypol. The liver had the highest tissue concentration of both enantiomers, and accumulation of (+)-gossypol was higher than (−)- gossypol in all tissues examined. No racemization of the enantiomers was apparent in the tissues analyzed. Our results indicated that both gossypol enantiomers were toxic to broilers but that (−)-gossypol was more harmful to efficient broiler production than (+)-gossypol.